ANTARCTIC BIOPROSPECTING: IS IT COMPATIBLE WITH THE VALUE OF ANTARCTICA AS A NATURAL RESERVE? - VIGNI, PATRIZIA (HART PUBLISHING, 2006)
Is bioprospecting consistent with Antarctic Treaty norms? What provisions would be necessary to adopt? Are other international treaties applicable to the Antarctic Treaty area?